2017
DOI: 10.1080/01443615.2017.1323197
|View full text |Cite
|
Sign up to set email alerts
|

Self-collected cervicovaginal sampling for site-of-care primary HPV-based cervical cancer screening: a pilot study in a rural underserved Greek population

Abstract: In the present pilot study, the feasibility of a site-of-care cervicovaginal self-sampling methodology for HPV-based screening was tested in 346 women residing in underserved rural areas of Northern Greece. These women provided self-collected cervicovaginal sample along with a study questionnaire. Following molecular testing, using the cobas HPV Test, Roche, HPV positive women, were referred to colposcopy and upon abnormal findings, to biopsy and treatment. Participation rate was 100%. Regular pap-test examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…In a study of 20,000 women from low-income communities in France, where low compliance with recommended Pap smear screening leads to 3,000 new cases of cervical cancer and 1,000 deaths each year, only 2% of women underwent Pap testing, while 18.3% of women responded to an invitation for a self-collected specimen for HPV testing ( 69 ). A study involving 346 women from underserved rural areas of Northern Greece, of whom only 17.1% had been regularly participating in Pap smear screening, found that 100% were willing to self-sample, with 90% willing to self-sample regularly if this option was available ( 70 ). First Nations women in Canada have a sixfold higher incidence of cervical cancer due to lower participation rates in cervical cancer programs; in a pilot program among 49 First Nations women, self-sampling was well received and the quality of samples was excellent ( 71 ).…”
Section: Self-sampling May Increase Cervical Cancer Screening Particimentioning
confidence: 99%
“…In a study of 20,000 women from low-income communities in France, where low compliance with recommended Pap smear screening leads to 3,000 new cases of cervical cancer and 1,000 deaths each year, only 2% of women underwent Pap testing, while 18.3% of women responded to an invitation for a self-collected specimen for HPV testing ( 69 ). A study involving 346 women from underserved rural areas of Northern Greece, of whom only 17.1% had been regularly participating in Pap smear screening, found that 100% were willing to self-sample, with 90% willing to self-sample regularly if this option was available ( 70 ). First Nations women in Canada have a sixfold higher incidence of cervical cancer due to lower participation rates in cervical cancer programs; in a pilot program among 49 First Nations women, self-sampling was well received and the quality of samples was excellent ( 71 ).…”
Section: Self-sampling May Increase Cervical Cancer Screening Particimentioning
confidence: 99%
“…Therefore, it was clear that the majority of women preferred self-sampling over physician sampling. Studies in rural areas where there is limited access to health institutions such as those reported by Esber et al [9] and Chatzistamatiou et al [12], for example, reinforce the preference for self-sampling, with over 60 and 86.6% of women expressing primacy for this method, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…(11) Were outcome measures (dependent variables) clearly defined, valid, reliable, and consistently implemented across all study participants? (12) Were the study evaluators blinded to the participants' exposure status? (13) Was the follow-up loss after baseline 20% or less?…”
Section: Types Of Sampling Methods Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Pap smear screening, found that 100% were willing to self-sample, with 90% willing to 250 self-sample regularly if this option was available (Chatzistamatiou et al 2017). First 251 Nations women in Canada have a six-fold higher incidence of cervical cancer due to 252 lower participation rates in cervical cancer programs; in a pilot program among 49 First 253 Nations women, self-sampling was well received and the quality of samples was 254 excellent (Zehbe et al 2011).…”
Section: Hc2 Hpv Assay and Several Pcr Amplification-based Tests Sucmentioning
confidence: 99%